Efficacy and safety of ipilimumab therapy in patients with metastatic melanoma: a retrospective multicenter analysis - Wiater, Katarzyna; Świtaj, Tomasz; Mackiewicz, Jacek; Kalinka-Warzocha, Ewa; Wojtukiewicz, Marek; Szambora, Paweł; Falkowski, Sławomir; Rogowski, Wojciech; Mackiewicz, Andrzej; Rutkowski, Piotr (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : The Patient Assistance Program, a type of expanded access program, was initiated for compassionate purposes to provide ipilimumab to patients with unresectable stage III or IV melanoma with failed previous treatment. The aim of this analysis is to evaluate efficacy, safety, and tolerability of ipilimumab therapy in daily clinical practice. Material and methods : We analyzed 50 patients (29 males, 21 females) aged 21 to 76 years (median: 49 years). An ipilimumab dose of 3 mg/kg was administered intravenously every 3 weeks for a total of 4 doses. Patients were assessed for response rate, progression-free survival and overall survival, and monitored for adverse events. Results : The objective response (complete or partial response) rate was 12%. Median overall survival was 8 months and median progression-free survival was 3 months. In patients with ECOG-PS 0, the median overall survival was 16 months. Immune-related adverse events (irAEs) occurred in 48% of the patients, grade 3 or 4 irAEs were reported in 8% of the patients, and there were no toxic deaths. Conclusions: Ipilimumab demonstrated clinical benefit in previously treated advanced melanoma patients. Although clinical benefit is limited to a minority of the patients, there is a benefit in terms of overall survival in this group of patients.